MICROBIOLOGICAL CORROSION OF METALS AND METHODS OF PROTECTION FROM IT - Erkhan Turgunov; Mashkura Mavlani; Ra’no Qo‘chqorova; Kuzibay Kultayev; Asadulla Minarov (The Bioscan, 2024)
The problems of microbiological corrosion of metals and ways of protection against it are considered. Methods for protecting metals from bio corrosion are based on the use of chemical biocides, as well as on the rational selection and use of acetylene compounds